6+(n-4)=2(2n+13)

Simple and best practice solution for 6+(n-4)=2(2n+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+(n-4)=2(2n+13) equation:


Simplifying
6 + (n + -4) = 2(2n + 13)

Reorder the terms:
6 + (-4 + n) = 2(2n + 13)

Remove parenthesis around (-4 + n)
6 + -4 + n = 2(2n + 13)

Combine like terms: 6 + -4 = 2
2 + n = 2(2n + 13)

Reorder the terms:
2 + n = 2(13 + 2n)
2 + n = (13 * 2 + 2n * 2)
2 + n = (26 + 4n)

Solving
2 + n = 26 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
2 + n + -4n = 26 + 4n + -4n

Combine like terms: n + -4n = -3n
2 + -3n = 26 + 4n + -4n

Combine like terms: 4n + -4n = 0
2 + -3n = 26 + 0
2 + -3n = 26

Add '-2' to each side of the equation.
2 + -2 + -3n = 26 + -2

Combine like terms: 2 + -2 = 0
0 + -3n = 26 + -2
-3n = 26 + -2

Combine like terms: 26 + -2 = 24
-3n = 24

Divide each side by '-3'.
n = -8

Simplifying
n = -8

See similar equations:

| 3*x^2+2=50 | | 10h-8h=h+25 | | 18=-4x-2+4 | | 44=4(n+3)+4n | | 3y-20=30 | | 9x8/9 | | 23g=7.13 | | 3x+6=-18-3x | | 4-(p-1)+4p+7=p+4 | | 9+12x=-24+x | | 12x+17=13x+8 | | 2[t-(9-2t)]=4(2t-4) | | 6x+5y-1=10 | | 7x+1=-6+8x | | -24+x=x+13 | | 4x+12=36-6x | | 6(-s-6)-3(6s-3)=s+8+3s | | 193=41*1+0.40x | | -1.4+(-5.7)= | | 6t-24=0 | | X+76+110=180 | | 8x+9(.25x)=10 | | -2+26x=25x | | 4*8.4+8*0.8=40 | | -3-s=4tj+19 | | 8(1.25-1.125x)+9x=10 | | 4*12+8*0.8=40 | | 24=m-15 | | 4*10+8*0.8=40 | | 4*4.6+8*0.8=40 | | 16x+12y=136 | | b=32(1600) |

Equations solver categories